Development of Web Programming Interactive Learning Multimedia in Vocational Middle School - Alam, Alfikri; Astuti , Indri; Suratman, Dede (Lembaga Penelitian dan Pengabdian kepada Masyarakat, Universitas Negeri Jakarta, 2022)
The research aimed to develop interactive multimedia learning on web programming materials in Vocational High schools. This research was conducted at SMK Negeri 1 Sajingan Besar, with the research subjects were students in class XI of Software Engineering expertise competency as many as 48 students. The research method used is a 4D model consisting of four stages, namely define stage, design, develop, and disseminate. Interactive learning multimedia developed validated by three media experts with an average result of 3.9 with a category of